The financing dynamics of newly founded firms - Hirsch, Julia; Walz, Uwe (Journal of Banking & Finance, 2019)
We aim to extend the sparse knowledge on the financing dynamics of newly founded firms by investigating 2456 French manufacturing firms that were founded between 2004 and 2006. Our data comes from their legally required and reported financial statements. We observe significant heterogeneity in the financing decisions at foundation and analyze whether these differences widen or converge by using different convergence concepts. We consistently find β-convergence that indicates the initial financing decisions have a negative effect on the accumulation of this source of financing. After investigating the development of variation in financing patterns across firms over time (σ-convergence), we find mixed results. While differences in debt composition (e.g. role of trade credit, bank loans as well as relation between short and long-term debt) vanish over time the opposite is true for debt-equity mixes.